A problem of finding an acceptable variant in generalized project networks. Issue 2 (25th July 2005) - Blokh, David; Gutin, Gregory; Yeo, Anders
Abstract : A project network often has some activities or groups of activities which can be performed at different stages of the project. Then, the problem of finding an optimal/acceptable time or/and optimal/acceptable order of such an activity or a group of activities arises. Such a problem emerges, in particular, in house-building management when the beginnings of some activities may vary in time or/and order. We consider a mathematical formulation of the problem, show its computational complexity, and describe an algorithm for solving the problem.